Willow [videorecording (DVD)] - Dolman, Bob; Kilmer, Val, 1959-2025; Whalley, Joanne, 1964-; Davis, Warwick; Marsh, Jean (LucasFilm, 2019)
A timeless fantasy tale where heroes come in all sizes. While Willow Ufgood finds an abandoned baby girl, he learns she is destined to end the reign of wicked Queen Bavmorda. Willow teams up with a rogue swordsman to protect the child against the darkness. Filled with magic and danger, this is the ultimate story of good versus evil.